Evaluasi Penggunaan Emulsi Lilin Pada Pemasaran Buah Mangga Arumanis - Yuniarti Yuniarti; Suhardjo Suhardjo; A. Suryadi; Bonimin Bonimin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1994)
Objective of this research was to know local and export consumer acceptability towards the use of 6% wax emulsion on mango arumanis cv. Fruits were harvested from Keaton experimental station, Pasuruan in October 1992. For local market, 30 bamboo baskets, each consisted of 15 kg of arumanis mango, 15 baskets were treated with wax emulsion and 15 baskets left no treated transported as far as ± 1000 km and observed at fruit markets. For export market, 30 carton box each consisted of 5 - 6 kg mango arumanis cv., 15 box were treated with wax emulsion and 15 box left no treated, exported to Singapore through Cirebon harbour and observed after they were arrived in Singapore. Obsersvation had been done on consumer acceptability, percent of damage, fruit condition, weight loss, stage of maturity and economical analysis. The results showed that for marketing that needed long time (± 134 hours), treatment of 6% wax emulsion could be accepted by the consumer, and price accepted by the retailer 0,9% higher each kg, compared to untreated.